A Very Compact and Sharp Roll-Off Low-Pass Filter with Four Transmission Zeros - Yang Xiao; Lin Li (Active and Passive Electronic Components)
A novel structure with sharp roll-off, wide stopband, and very compact size is presented in this paper. By combining a capacitor-embedded transmission line ring and two shunt open stubs, this structure exhibits a high-performance three-pole low-pass filter (LPF) response with four generated transmission zeros. With the help of these four transmission zeros, the proposed LPF achieves improved roll-off rate, extended stopband, and significantly very compact size. To verify the feasibility of the proposed structure, a prototype LPF having the cut-off frequency at 0.63 GHz is designed, fabricated, and measured as an illustrative example. Final result shows that a roll-off rate of 109.3 dB/GHz along with a relative stopband bandwidth of 114.6% can be obtained. Moreover, the filter dimensions are as small as 15.7 mm × 26.9 mm, that is, 0.004λg2, where λg is the guided wavelength at the cut-off frequency. The filter structure is simple and easy to fabricate as well.